Mapping the field through bibliometric analysis of passenger centric railway transportation. (2016) - Kadam, Sanjeev; Bandyopadhyay, Prabir Kumar; Patil, Yogesh
Railway transportation is considered to be the most preferable public transportation mode worldwide. Indian cities like Delhi Mumbai, Kolkata and Chennai do have either metro trains or suburban trains or combinations of both. The demand for suburban train services in Indian metro cities is continuously increasing. This paper is an attempt to conduct systemic mapping of the available literature with respect to interactions between passengers and railway transportation. This bibliometric analysis has extensively used repositories such as Scopus, Google Scholar, Researchgate, and tools like Gephi, Sciencescape, Table2Net and GPS Visualizer. The study revealed that maximum studies on passenger centric railway transportation have taken place in the recent years and collaboration among researchers is a common aspect. It was also observed that Chinese universities/institutions are leading in the research studies concerning passenger centric railway transportation. Keywords statistics indicates less attentiveness of researchers towards passenger comfort, satisfaction, movements and behaviour.